Pengaruh Kualitas Layanan terhadap Loyalitas dengan Kepuasan Nasabah sebagai Variabel Mediasi : Studi pada PT. Bank Jatim Cabang Kota Batu - Moch. Sokeh (Universitas Kristen Indonesia Toraja, 2024)
Customer satisfaction has become a central concept in marketing theory and practice, and is one of the essential goals for business activities. Basically, customer satisfaction and dissatisfaction with a product or service will affect subsequent customer behavior. Customers who are satisfied will show a high probability of customers returning to use the same product or service. According to Syah (2021), satisfied customers also tend to provide good references to the product or service to others. Meanwhile, dissatisfied customers can cause negative attitudes towards the brand or manufacturer or service provider, even distributors, reduced likelihood of repeat purchases, brand switching, and various types of complaint behavior.